Clinical Practice Changes in the Diagnosis and Management of Bacterial Tracheitis in Ventilator-Dependent Children in the Outpatient Setting After Introduction of a Novel Pathway - Geneviève A Donahey; Glenn J Rapsinski (Journal of the Pediatric Infectious Diseases Society, 2026)
Abstract Background Diagnosis and management of bacterial tracheitis (BT) in tracheostomy- and ventilator-dependent children (VC) is highly variable among outpatient subspecialty providers (OP). Stewardship efforts are generally limited to the inpatient setting, thus further studies are needed to examine and improve outpatient practices. Many OP report desire for guidance in the diagnosis and management of BT and feel a decision support tool would be helpful in their daily practice, thus we developed a pathway for use in the outpatient setting and endeavor to examine its impact on clinical practice. Methods This is a quality improvement project involving stepwise implementation of a novel pathway for diagnosis and management of BT starting 10/1/2024. Stakeholders in each subspeciality, Pulmonology, Complex Care, and Otolaryngology (ENT), were identified and education regarding diagnosis and management of BT was performed. Pathway was subsequently distributed to the OP departments. VC following with OP at the Children’s Hospital of Pittsburgh (CHP) were identified and chart review performed from 1/1/2022-9/30/2025 examining outpatient interactions for respiratory illness events (RIE) and subsequent management decisions made by OP prior to and after pathway implementation. Results After introduction of pathway, there was no change in number of RIE with outpatient involvement per patient per month, 1.07 ± 0.02 versus 1.08 ± 0.05 (median ± 95% confidence interval). There was an increase in involvement of Pulmonology OP (51.38% versus 76.36%). Rates of respiratory cultures meeting criteria per pathway increased after pathway introduction. Antibiotic regimen was changed more frequently to reflect organisms grown in EAC after pathway introduction. Fewer antibiotic courses were prescribed for RIE (57.89% versus 50.30%), however antibiotic duration of therapy (DOT) was not changed after pathway introduction. Conclusion Initial outcomes suggest introduction of a pathway for diagnosis and management of BT results in more standardized practices, especially more consistent EAC ordering practices and appropriate antibiotic choices to reflect EAC results. Antibiotic DOT was not appreciably affected, suggesting further investigation is needed to decrease excessive antibiotic prescriptions.